Pengembangan E-Learning Berbasiskan LMS untuk Sekolah, Studi Kasus SMA/SMK di Sumatera Utara - Roni Yunis; Kristian Telaumbanua (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2017)
This study develops an e-learning system customized to the needs of high school/vocational school level, with a case study of two schools in North Sumatra. E-learning system is developed using Learning Management System (LMS) eFront which is modified according to user requirements. To obtain the results of the e-learning development, a good implementation plan is required, thus, it is necessary to have a good training and evaluation to assess the ability and understanding of the users in using the e-learning system. Evaluation is conducted by measuring and analyzing the results of pre-test and post-test using statistical approach with SPSS 19. A good implementation plan of the e-learning system needs to be prepared at earliest possible stage, including resource readiness, availability of system services, and information technology infrastructure. The results of evaluations are used for decision making related to the implementation of e-learning in schools. The results show that users ability in using e-learning increase significantly, with the mean value of -12.89.